2022
DOI: 10.21926/obm.icm.2203037
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Literature Review on Compassion-Focused Therapy for Individuals with Intellectual Disability

Abstract: Individuals with intellectual disabilities (ID) are at a higher risk of shame and self-criticism and tend to make downward social comparisons. Compassion-focused therapy (CFT) is commonly used to address these issues in the general population, however, information on the adaptability and effectiveness of CFT for individuals with ID is limited. Thus, we conducted a scoping review of studies on CFT for individuals with ID, to accumulate and consolidate the information and provide a basis for future studies to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…There is, however, emerging evidence that CFT can be meaningfully adapted for people with ID (Cooper and Frearson, 2017; Goad, 2023) and lead to reductions in psychological distress (Rawlings et al , 2021; Willems et al , 2022).…”
Section: Compassion-focused Therapy and Its Use Within Intellectual D...mentioning
confidence: 99%
See 1 more Smart Citation
“…There is, however, emerging evidence that CFT can be meaningfully adapted for people with ID (Cooper and Frearson, 2017; Goad, 2023) and lead to reductions in psychological distress (Rawlings et al , 2021; Willems et al , 2022).…”
Section: Compassion-focused Therapy and Its Use Within Intellectual D...mentioning
confidence: 99%
“…Furthermore, group environments allow people to share experiences, receive validation or encouragement, develop socioemotional intelligence (Goad, 2023) and learn new ways of coping (Bates, 2005), which may help reduce shame. Studies have explored the acceptability and effectiveness of group CFT for people with ID (Clapton et al , 2018a; Goad and Parker, 2021; Hewitt et al , 2023; Willems et al , 2022). These studies demonstrate that CFT can be effectively adapted for people with ID and acceptably delivered in a group context.…”
Section: Group Compassion-focused Therapy For People With Intellectua...mentioning
confidence: 99%
“…There is a growing literature around using CFT with people with intellectual disabilities Cowles et al (2020). A subsequent review of CFT with people with intellectual disabilities found that while adapted CFT can effectively reduce self‐criticism and downwards social comparison, robust research protocols are lacking in the literature (Willems et al, 2022). Additional strategies for improving the accessibility of CFT for this client group have been developed (e.g., Goad, 2023; Lucre & Clapton, 2021), which assist clinicians when designing interventions.…”
Section: Introductionmentioning
confidence: 99%